2014
DOI: 10.2147/oajsm.s58005
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported concussion history: impact of providing a definition of concussion

Abstract: BackgroundIn recent years, the understanding of concussion has evolved in the research and medical communities to include more subtle and transient symptoms. The accepted definition of concussion in these communities has reflected this change. However, it is unclear whether this shift is also reflected in the understanding of the athletic community.What is known about the subjectSelf-reported concussion history is an inaccurate assessment of someone’s lifetime exposure to concussive brain trauma. However, unfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 17 publications
2
81
1
1
Order By: Relevance
“…It is also possible that retrospective self-reporting of concussion history introduces significant error variance. 29 As stated previously, self-reported concussion history was not associated with cortical thickness. Follow-up analysis, however, revealed an "Age by Concussion History" interaction on cortical thickness in right ventrolateral prefrontal and right parietal regions.…”
Section: Discussionmentioning
confidence: 53%
“…It is also possible that retrospective self-reporting of concussion history introduces significant error variance. 29 As stated previously, self-reported concussion history was not associated with cortical thickness. Follow-up analysis, however, revealed an "Age by Concussion History" interaction on cortical thickness in right ventrolateral prefrontal and right parietal regions.…”
Section: Discussionmentioning
confidence: 53%
“…Third, previous work has demonstrated that the operational definition of concussion can influence athletes' self-report of previous concussions. 56 The reliance on self-reported medically diagnosed concussions in the current work may have led to under-estimation, as many concussions go unreported. 57 Although we observed no significant relationship between the number of concussions and cortical thickness in football athletes with a history of concussion, alternative cutoff points (e.g., three or more concussions) and larger sample sizes should be used in future studies to investigate potential exposuredependent relationships with neuroanatomical measures.…”
Section: Limitationsmentioning
confidence: 99%
“…Control subjects were excluded if they had ever served in the military or had ever participated in any of the following organized sports: football, hockey, rugby, soccer, lacrosse, wrestling, boxing, basketball, gymnastics, martial arts, kickboxing, cycling, or distance running. Medical conditions that led to the exclusion of controls included self-reported history of concussion, 29 diagnosis of dementia, or medication that would make lumbar puncture unsafe.…”
Section: Participantsmentioning
confidence: 99%